118k views
3 votes
Solve the equation. 3p – 1 = 5(p – 1) – 2(7 – 2p) 3 -9 -10 0

User Chris Voss
by
5.9k points

1 Answer

3 votes

Answer:


Explanation:

3p – 1 = 5(p – 1) – 2(7 – 2p) 3 -9 -10 First Distribute

3p-1= 5p-5-42+12p-9-10 Simplify all like factors

3p-1=17p-66 Add 66 on both sides

3p+65=17p Subtract 3p from both sides

65=15p Divide both sides by 15

p=4.3

if it is a 100

3p – 1 = 5(p – 1) – 2(7 – 2p) 3 -9 -100 First Distribute

3p-1= 5p-5-42+12p-9-100 Simplify all like factors

3p-1=17p-156 Add 156 on both sides

3p+155=17p Subtract 3p on both sides

155= 15p divide both sides by 15

10.3=p

User Jwueller
by
6.2k points